2000
DOI: 10.1055/s-2000-7754
|View full text |Cite
|
Sign up to set email alerts
|

How asymptomatic is asymptomatic primary hyperparathyroidism?

Abstract: We observed several cases of patients who believed they were free of symptoms or signs of primary hyperparathyroidism (pHPT) preoperatively. reported a change of complaints following parathyroidectomy (PTX). We, therefore, decided to examine a larger group of patients to discover if these findings were incidental or of more general significance. The role of PTX in these patients with asymptomatic pHPT remains controversial. In 1991 criteria were defined at a NIH-consensus conference, according to which patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 19 publications
2
40
0
3
Order By: Relevance
“…On the other hand, the benefit of a surgical parathyroid excision in patients in fairly good clinical condition is debated [7]. Some authors suggest a surgical approach in the case of mild nonspecific symptoms, because the symptomatology usually disappears after operation [10, 11, 12]. Other authors recommend surgery only for patients with PTH values higher than 150 pg/ml [13], or for subjects younger than 50 years with serum calcium concentrations greater than 12 mg/dl, marked hypercalciuria (>400 mg/day) and reduction in bone density [14].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the benefit of a surgical parathyroid excision in patients in fairly good clinical condition is debated [7]. Some authors suggest a surgical approach in the case of mild nonspecific symptoms, because the symptomatology usually disappears after operation [10, 11, 12]. Other authors recommend surgery only for patients with PTH values higher than 150 pg/ml [13], or for subjects younger than 50 years with serum calcium concentrations greater than 12 mg/dl, marked hypercalciuria (>400 mg/day) and reduction in bone density [14].…”
Section: Discussionmentioning
confidence: 99%
“…нефролитиаз выявляют у 15-34% пациентов, по не-которым данным до 45%; язвы желудка и/или двенадцати-перстной кишки встречаются в 10-15% случаев [6,7,9,13]. анализируя собранные анкеты, нами было получено, что не-фролитиаз встречается у 45% пациентов, язвенная болезнь -у 18% пациентов.…”
Section: результаты и обсуждениеunclassified
“…от 9,4 до 81% пациентов име-ют нарушения в психоэмоциональной сферы (бессонница, вялость, сонливость, раздражительность, тревожность, де-прессивность, снижение памяти) в качестве ведущего про-явления пгпт. так же среди прочих проявлений пгпт ча-сто обсуждаются инсипидарный синдром, желчекаменная болезнь, кальцификация сосудов и клапанов сердца [6,11]. результаты нашего исследования по частоте таких проявле-ний у пациентов с пгпг представлены на рисунке 8. они свидетельствуют о том, что пациент с пгпт может обра-титься к врачам любой специальности (терапевту, ревмато-логу, урологу, нефрологу, неврологу, ортопеду-травматоло-гу, кардиологу и др.)…”
Section: результаты и обсуждениеunclassified
“…PHPT is a chronic disease displaying various clinical courses. By definition (2), only very few are 'asymptomatic' (i.e., free of symptoms, no organ manifestations even after careful screening) (3).…”
Section: Introductionmentioning
confidence: 99%
“…However, multivariate analysis has not identified a single or a set of biochemical parameters that would allow predicting the clinical course of these subjects (3). Careful analysis of patients has revealed that postoperative metabolic complications occur in those with a long history of PHPT.…”
Section: ) No Alteration In Renal Function (Creatinine Clearancementioning
confidence: 99%